In Vitro Antioxidant and Anti-Colon Cancer Activities of Sesamum indicum L. Leaf Extract and Its Major Component, Pedaliin - Seoyun Kim; Hyi Young Yang; Hwa Jin Lee; Jihyeung Ju (Foods, 2021)
Sesame (Sesamum indicum L.) leaves (SLs) are used as vegetables and traditional medicines in Asian and African countries. We investigated in vitro antioxidant and anti-colon cancer efficacy of ethanol extract of SL (SLE) and its major bioactive component. SLE contained appreciable amount of major classes of antioxidant phytochemicals, such as total polyphenols, total flavonoids, and carotenoids, and correspondingly exhibited antioxidant activities, such as radical scavenging activity and ferric reducing antioxidant power (FRAP). A cell viability assay showed that SLE time- and dose-dependently attenuated the growth of human colon cancer cells, HT29 and HCT116. Flow cytometry analysis showed that SLE increased sub-G1 (in HT29 and HCT116) and G2/M (in HCT116) cell populations, suggesting that the growth inhibition by SLE was due to induction of apoptosis and G2/M cell cycle arrest. Trans-well and wound-healing assays showed that SLE alleviated invasion and migration of HT29 and HCT116 cells in non-cytotoxic conditions. High-performance liquid chromatography analysis revealed that pedaliin (6-hydroxylueolin 7-methyl ether 6-glucoside; pedalitin-6-O-glucoside) was a major constituent of SLE. Moreover, FRAP, growth-inhibitory, anti-invasive, and anti-migratory activities of pedaliin were found. These results demonstrated that SLE possesses in vitro antioxidant and anti-colon cancer activities and that pedaliin is a major component contributing to such activities.